Quality education for all end exclustion now! (Lao dong Xa hoi, 2009)
On 23rd April 2008, millions of students, teachers, parents and politicians in 64 provinces throughout Vietnam joined with partners for 120 countries from around the world to observe Global Action Week for education (GAW) 2008. This event was recorded in the Guinness Book of Records as the "World's Biggest Lesson". The table of content" is including 5 parts: 1-Global campaign for education ; 2-Global action week for education ; 3-Why do students drop out of school? ; 4-How to attract students to school ; 5-Conclusions and recommendations.